Dynamic range extension of the Tibet underground muon detectors for measurements up to the knee energy region with 3-inch photomultipliers. (16th June 2021) - Lin, Y.H.; Huang, J.; Chen, D.; Ohnishi, M.; Zhang, Y.; Zhai, L.M.; Chen, X.; Fang, J.H.; Meng, Y.
Abstract: Aiming to study the primary cosmic-ray mass composition up to the knee energy region with the Tibet underground water-Cherenkov muon-detector array (MD), we propose to extend the dynamic range of each MD detector with an 8-inch PMT (Beijing Hamamatsu CR365) and a 3-inch PMT (HZC XP72B22). We carried out a series of tests on the candidate 3-inch XP72B22 PMT to examine whether it can meet our requirements. The measurement results showed that the XP72B22 has a wide dynamic range of 3 orders of magnitude and a linear response up to ∼10 5 photoelectrons (PEs) at the supply voltage of 700 V. Combined with previous test results of the CR365, these two types of PMT can achieve an equivalent dynamic range from 30 to 10 6 PEs. As a result, an MD cell is able to detect cosmic rays around the knee energies by adding the CR365 and the XP72B22.